Keadilan, Amanah, dan Musyawarah: Integrasi Nilai Kepemimpinan Islam dalam Manajemen Pendidikan Modern - Amelia Nur Rochim; M Imamul Muttaqien (Jurnal Visi Manajemen, 2025)
Leadership plays an essential role in determining the success of an organization, especially in the field of education. In the context of educational management, a leader not only performs administrative functions but also inspires and motivates all elements within the institution. A well-led educational environment can support individual potential development and encourage innovation. The Islamic perspective views leadership as a trust (amanah) that must be carried out with justice, integrity, and moral responsibility. Islamic principles such as trustworthiness, justice, consultation (shura), and noble character serve as a foundation for leaders to make inclusive and fair decisions, enhancing the effectiveness of educational management. This research uses a literature study method to analyze the application of Islamic leadership values in educational management. The findings show that Islamic values in leadership can strengthen motivation, participation, and innovation within educational environments and foster positive character in students and educators. Thus, integrating Islamic values into educational leadership is crucial in forming a generation that is intellectually capable, moral, and faithful.